Prospects of Using the Technology Critical Thinking Formation at the University Lectures - Artyushina, Maryna (Pedagogical Discourse, 2013)
The article is dedicated to the problem of necessity to update teaching technologies at the university. The possibility of using technology of critical thinking formation at the lectures is shown. The content of this technology, which consists of three phases is determined: call, reflection and introspection. The definition of the concept of a critical-analytical lecture is given. Its stages and tasks of each stage are revealed. The list of methods and techniques that can be used at different stages of the critical-analytical lecture is made. The problems and obstacles of implementation of technology of critical thinking formation at the lectures are shown. Students’ comments about the effectiveness of this technology in real learning process are given.